Convenient access to the tricyanoborate dianion B(CN)32− and selected reactions as a boron-centred nucleophile1. Issue 24 (25th March 2015) - Landmann, Johannes; Sprenger, Jan A. P.; Bertermann, Rüdiger; Ignat'ev, Nikolai; Bernhardt-Pitchougina, Vera; Bernhardt, Eduard; Willner, Helge; Finze, Maik
<x xml:space="preserve">Abstract</x> Tricyanoborates M2B(CN)3 (M = Na, K) are accessible by reduction of tricyanofluoroborates with alkali metals in liquid ammonia or in THF–naphthalene.